A Comprehensive Review Of Multi-Omics, Network Pharmacology, And Artificial Intelligence Approaches To Heart Failure (Advances in Applied Biological Research, 2026)
Heart failure continues to be a pandemic of the twenty-first century, a major  contributor to which are chronic diseases and the increasing number of elderly  people. The transition from the outdated “dropsy” to the modern neurohormonal  theory of the illness is reviewed. Beta-blockers, MRAs, ARNIs, and SGLT2  inhibitors are the core “scaffold” of medicines that have improved nearly all  patient outcomes, which is why treatment has revolutionized itself. However, since  genetics recognizes the genetic variability of heart failure situations, it holds the  key to the sector’s future. The goal of this effort is to identify illness endotypes  for customized therapeutic care, driven by bioinformatics and multi-omics data.  On top of that, the scientists are keen on implementing the same technology and  in silico approaches to explore phytocomplexes with multitarget activity. AI and  machine learning have dramatically transformed the pharmaceutical industry,  disease prediction, and diagnostic procedures. This paper elucidates the evolution  of heart failure management from an indiscriminate, reactive model to a tailored,  systems-based, preventive paradigm.
Keywords: Heart Failure; Precision Medicine; Multi-Omics; Network Pharmacology; Artificial Intelligence; Molecular docking